Capitalizing on Organizational Knowledge: Imperatives for Decentralized Agricultural Extension Systems - Baconguis, Rowena (Silliman Journal, 2023)
Agricultural extension services have been organized to provide producers scientific farming technologies and knowledge to give them competitive edge in making farming decisions. Such an edge would have the effect of transforming the agriculture sector into a modern and profitable industry where the rural poor gradu-ate from poverty into the middle class. However, because such is not the case in many countries like the Philippines, extension systems worldwide have been un-der scrutiny for falling short of their objectives. The current study looked into a decentralized municipal agricultural extension system in a layer and swine based municipality—San Jose, Batangas, Philippines. Secondary data from 1993 (or two years after the enactment of the Decentraliza-tion Law) were complemented by interviews and focused group discussions. It was found that the municipality has active private extension for its swine and layer industry, the major source of agriculture income, but the government agricultural extension system needs to re-evaluate its traditional role from a monolithic pro-ducer of traditional services to that of an enabler where it catalyzes the effective involvement of public and private agencies or organizations to build the intellectual capital of the locality to make superior business decisions. Such a shift in perspec-tive by the municipality requires a shared vision among the key stakeholders in the community. It is argued that extension systems, whose function is primarily to develop human capacities in agriculture, need to maximize strategies to create knowledge that addresses the multi-functional nature of agricultural develop-ment. Knowledge creation strategies should be prioritized as these could signifi-cantly improve extension's contribution to facilitating a learning community adept at addressing complex problems at the municipality level.